Toward optimization using unsteady CFD simulation around kayak hull - Leroyer, A.; Duvigeau, R.; Queutey, P.; Crochet, J.-P.; Rouffet, C. (Procedia Engineering, 2016)
The aim of this research work is to develop a procedure including experimental measurements and advanced numerical simulations of fluid flow to address optimization problems in kayaking. The different steps preparatory to the optimization task are described: the use of experimental data on the hull kinematics to create a simplified, periodic but realistic kinematic model, the numerical simulation using this kinematics as an imposed hull motion, the a posteriori computation of the loads of the athlete acting on the hull. Finally, a verification of the whole chain is carried out, by solving the flow around the hull, which is now free to move according to the computed loads of the athlete. Some preliminary results of this on-going work are finally shown.